2017
DOI: 10.7717/peerj.3925
|View full text |Cite
|
Sign up to set email alerts
|

The head turn paradigm to assess auditory laterality in cats: influence of ear position and repeated sound presentation

Abstract: In most humans, speech is predominantly processed by the left hemisphere. This auditory laterality was formerly thought to be an exclusive human characteristic, but is now suggested to have pre-human origins. In studies on auditory laterality in nonhuman animals, the head turn paradigm has become very popular due to its non-invasive character. Although there are implications that the head turn direction indicates functional dominance of the contralateral hemisphere in processing a given sound, the validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Only in the last decades have parallels been sought and found in animals, revealing that brain lateralisation is a rather universal feature amongst vertebrates and some invertebrates [2][3][4][5]. Surprisingly, auditory laterality is amongst the latest studied aspects, but these studies have shown that there are clear asymmetries for processing, in particular species-specific sound signals, in vertebrates [6][7][8][9]. Most of these studies have investigated whether animals, as a parallel to language processing, had a dominant hemisphere for the processing of the species-specific vocalisations.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the last decades have parallels been sought and found in animals, revealing that brain lateralisation is a rather universal feature amongst vertebrates and some invertebrates [2][3][4][5]. Surprisingly, auditory laterality is amongst the latest studied aspects, but these studies have shown that there are clear asymmetries for processing, in particular species-specific sound signals, in vertebrates [6][7][8][9]. Most of these studies have investigated whether animals, as a parallel to language processing, had a dominant hemisphere for the processing of the species-specific vocalisations.…”
Section: Introductionmentioning
confidence: 99%